Active engagement with assessment and feedback can improve group-work outcomes and boost student confidence. Issue 1 (1st January 2017) - Scott, G. W.
Abstract: This study involves evaluation of a novel iterative group-based learning task developed to enable students to actively engage with assessment and feedback in order to improve the quality of their written work. The students were all in the final semester of their final year of study and enrolled on either BSc Zoology or BSc Marine and Freshwater Biology at a mainstream UK university, but the findings of this research can be generalised to a wider student body. The main findings are that in a group work context, individual students can use provided assessment criteria to accurately assess the work produced by their group and that their ability to produce and recognise work of a higher quality improves as a result of a social dialogue around self/peer assessment and self/tutor generated feedback. The study also reveals that producing poorer work over-assess and those achieving the highest marks under-assess. Over-assessing students focus to a greater extent upon the superficial deficiencies in their work, whereas under assessing students are more likely to focus on more significant issues. High-achieving under-assessing students lack confidence in their own abilities, but believe feedback provides a confidence boost.